The Impact Of Blooket On Vocabulary Achievement Of Grade XI MIPA 2 Students At SMA Sutojayan - Alen Isha Kinanti; Hesty Puspita Sari (Jurnal Riset Rumpun Ilmu Bahasa, 2024)
Vocabulary, comprising words acknowledged by individuals or inherent to a particular language, is essentially a collection of linguistic elements. Vocabulary is being an important element to support students’ competence in English. The aim of this study is to examine and enhance students' vocabulary achievement at SMAN 1 Sutojayan, specifically in class XI MIPA 2, using Blooket as a learning tool. In this research, a quantitative methodology is utilized, employing a one-group pre-test post-test design. The research subjects consist of 35 students from class XI MIPA 2. The findings of this investigation demonstrate that the null hypothesis (Ho) was disapproved, while the alternative hypothesis (Ha) was affirmed, revealing a notable mean disparity between pre-test and post-test results. This research provides a deeper understanding of the importance of enriching students' vocabulary during the learning process, as well as establishing a strong foundation for the development of more effective teaching strategies to enhance students' vocabulary comprehension in the future. The findings of this study can be a valuable contribution to efforts aimed at improving the quality of education at SMAN 1 Sutojayan and similar educational institutions. Future research is highly recommended to explore an other tool for students’ vocabulary improvement.